2021
DOI: 10.1007/s42995-021-00101-2
|View full text |Cite
|
Sign up to set email alerts
|

The intriguing chemistry and biology of sulfur-containing natural products from marine microorganisms (1987–2020)

Abstract: Natural products derived from marine microorganisms have received great attention as a potential resource of new compound entities for drug discovery. The unique marine environment brings us a large group of sulfur-containing natural products with abundant biological functionality including antitumor, antibiotic, anti-inflammatory and antiviral activities. We reviewed all the 484 sulfur-containing natural products (non-sulfated) isolated from marine microorganisms, of which 59.9% are thioethers, 29.8% are thia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(40 citation statements)
references
References 357 publications
0
40
0
Order By: Relevance
“…The bioactivity found in the Streptomyces strains detected in this work may be justified by the action of molecules such as diketopiperazines, N-acetyltyramine, antibiotic MKN-003B, germicidin G, surugamide A and E, blastmycin, antimycins A11 and A13, ansalactam A, corynecin I and chloramphenicol, as well as non-identified molecules such as C 13 H 22 O 3 , C 20 H 13 N 3 O 6 , C 22 H 44 O 12 , C 27 H 53 N 5 O 10 and C 23 H 13 ClO 4 S 2 . This last molecule seems to be of special interest, as the presence of a halogen (chlorine) and two sulphur atoms may indicate potential bioactivity [ 119 , 120 ]. Overall, these results suggest the relevance of the genus Streptomyces for the discovery of natural products and drug discovery research, as the extracts of the strains studied here showed antibacterial activity and putatively contain bioactive compounds and possible novel natural products.…”
Section: Discussionmentioning
confidence: 99%
“…The bioactivity found in the Streptomyces strains detected in this work may be justified by the action of molecules such as diketopiperazines, N-acetyltyramine, antibiotic MKN-003B, germicidin G, surugamide A and E, blastmycin, antimycins A11 and A13, ansalactam A, corynecin I and chloramphenicol, as well as non-identified molecules such as C 13 H 22 O 3 , C 20 H 13 N 3 O 6 , C 22 H 44 O 12 , C 27 H 53 N 5 O 10 and C 23 H 13 ClO 4 S 2 . This last molecule seems to be of special interest, as the presence of a halogen (chlorine) and two sulphur atoms may indicate potential bioactivity [ 119 , 120 ]. Overall, these results suggest the relevance of the genus Streptomyces for the discovery of natural products and drug discovery research, as the extracts of the strains studied here showed antibacterial activity and putatively contain bioactive compounds and possible novel natural products.…”
Section: Discussionmentioning
confidence: 99%
“…The well-known conotoxin, ecteinascidin 743 (ET-743), and penicillin are examples of natural sulfur-containing clinical drugs. Furthermore, many sulfur-containing drugs are derived from natural products, e.g., phthalascidin and ixabepilone for cancer treatments, rosuvastatin for hyperlipidemia, and dalfopristin and quinupristin for infectious diseases [7].…”
Section: Introductionmentioning
confidence: 99%
“…Investigating new bioactive natural products from marine fungi is a major and constant research focus in our laboratory [ 21 , 22 , 23 , 24 ]. Natural product researchers also face the challenge of targeting the discovery of bioactive compounds from a microbial resource library.…”
Section: Introductionmentioning
confidence: 99%